Territorialidades da intolerância religiosa: resistência cultural e o preconceito contra a Umbanda e o Candomblé em Ituiutaba - Minas Gerais - Souza, Leonardo Sebastião Delfino de (2021)
The religious diversity in Brazil allows us to live with a multiplicity of beliefs and creeds with different characteristics. Although Brazil is a predominantly Christian country, several other religions coexist in the same space, requiring mutual respect and religious tolerance with all denominations. However, in several circumstances, we perceive acts of prejudice and intolerance linked to the religious issue. The present research is justified by the contribution it gives to the theme, especially to Geography, and to leaders of African origin, highlighting the need for public policies aimed at the realization of rights inherent to the freedom of belief of religions of African-Brazilian origin. In addition, the research gives practitioners of these religions the chance to be heard, to report the whole process of prejudice and discrimination of which they have been victims for a long period. In this sense, this investigation aimed to understand the phenomenon of intolerance against religions of Afro-Brazilian origin, specifically Umbanda and Candomblé, in Ituiutaba - MG. It also aimed to discuss academic concepts about freedom of belief and religious intolerance in Brazil; to analyze the formation of Afro-Brazilian terreiro communities in Ituiutaba; investigate the existence of cases of religious prejudice against the terreiro communities; and to verify how the authorities (political, legal and police) deal with the possible records of religious intolerance in Ituiutaba. In the meantime, the methodology adopted was based on literature review, document analysis and fieldwork, with a qualitative approach. As for the treatment of data, the same happened through the search for literature that supported the study, linked to the elaboration of graphs, tables and maps from data collected in the interviews conducted with the priests of Umbanda and Candomblé in Ituiutaba. With these data, and after their subsequent analysis, a map was drawn up containing the geographical location of the religious temples surveyed in the fieldwork, as well as the religious intolerance facts narrated by the priests. Through the analysis of the interviews, it was found the existence of cases of intolerance and religious prejudice related to the religions object of the present study, the same being substantiated through verbal and psychological aggressions against the faithful of Umbanda and Candomblé. Despite the reported cases of religious discrimination, no physical or patrimonial aggression against Umbandistas and Candomblecistas was found, nor attacks on axé terreiros. In summary, it was found that, although there is a narrative of facts of religious intolerance in the reported cases, the Umbanda and Candomblé terreiros remain active, culturally resisting the attacks of intolerant and prejudiced individuals.